Comparative Responses to Metal Oxide Nanoparticles in Marine Phytoplankton - Castro-Bugallo, Alexandra; González-Fernández, África; Guisande, Cástor; Barreiro, Aldo (Archives of environmental contamination and toxicology, 2014)
A series of experiments was undertaken on three different marine microalgae to compare the effect of two metal oxide nanoparticles (NPs) on different physiological responses to stress: zinc oxide (ZnO), a known toxic compound for microalgae, and the never before tested yttrium oxide (Y₂O₃). The effect of these potential pollutants was estimated for different physiological variables and temporal scales: Growth, carbon content, carbon-to-nitrogen (C:N) ratio, and chlorophyll fluorescence were evaluated in long-term assays, and reactive oxygen species (ROS) production was evaluated in a short-term assay. Population growth was the most susceptible variable to the acute toxic effects of both NPs as measured in terms of number of cells and of biomass. Although Phaeodactylum tricornutum and Alexandrium minutum were negatively affected by ZnO NPs, this effect was not detected in Tetraselmis suecica, in which cell growth was significantly decreased by Y₂O₃ NPs. Biomass per cell was negatively affected in the most toxic treatments in T. suecica but was positively affected in A. minutum. ZnO treatments induced a sharper decrease in chlorophyll fluorescence and higher ROS than did Y₂O₃ treatments. The pronounced differences observed in the responses between the species and the physiological variables tested highlight the importance of analyzing diverse groups of microalgae and various physiological levels to determine the potential effects of environmental pollutants.